Does gut microbiota have an impact on the origin of Alzheimer's and Parkinson's disease? - literature review - Izabela Oleksak; Michał Leśniewski; Iwona Welian; Karolina Maliszewska; Joanna Ziółkowska (Kazimierz Wielki University, 2024)
Introduction and purpose: Among neurodegenerative disorders, Alzheimer's disease (AD) and Parkinson's disease (PD) are the most prevalent. It has been observed recently that alterations in the gut microbiota are associated with the onset of neurodegenerative disorders. This research aims to estimate the pathomechanisms and disease courses associated with the gut microbiota that lead to AD and PD development. Material and methods The following review was based on articles from the PubMed and Google Scholar databases. Key search terms included Alzheimer's disease; Parkinson's disease; gut microbiota; neurodegenerative diseases. State of knowledge The advancement of neurodegenerative processes is linked to the varying progressive course of both disorders. There are numerous likely reasons that connect the development of AD and PD and the gut microbiome. These include the hypotheses on inflammation, the decrease in the quantity of bacteria that produce short-chain fatty acids, and hygiene. The researchers' suggested treatment plans for the two illnesses are comparable. Conclusions A major influence on the development of neurodegenerative disorders is the gut microbiome. To clarify the precise connections between the gut microbiota and the development of AD and PD, further thorough research is required. More human research is required. Furthermore, it's possible that early interventions, such switching to a Mediterranean diet, are anticipated to lower the risk of AD or PD.